2018
DOI: 10.1111/add.14289
|View full text |Cite
|
Sign up to set email alerts
|

What defines a clinically meaningful outcome in the treatment of substance use disorders: reductions in direct consequences of drug use or improvement in overall functioning?

Abstract: The field of substance use disorders should include measures of negative psychosocial and health consequences of drug use, as opposed to overall functioning, in the effort to establish meaningful non-abstinence-based end-points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 47 publications
0
38
1
Order By: Relevance
“…As such, this body of literature may be well served by a patient‐level meta‐analysis (e.g., Lambert et al., ) if consistent outcome and patient characteristic measures were available. Also, this meta‐analysis selected consumption/abstinence measures a priori, but equally important may be consequences of alcohol use and improvements in overall functioning, particularly when examining primarily harm‐reduction studies (Kiluk et al., ).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…As such, this body of literature may be well served by a patient‐level meta‐analysis (e.g., Lambert et al., ) if consistent outcome and patient characteristic measures were available. Also, this meta‐analysis selected consumption/abstinence measures a priori, but equally important may be consequences of alcohol use and improvements in overall functioning, particularly when examining primarily harm‐reduction studies (Kiluk et al., ).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Third, as mentioned above, the use of a bounded outcome variable (NDA per week) imposes ceiling and floor effects. To address the constraints of ceiling and floor effects, future research might consider measuring a spectrum of outcome variables, such as psychosocial functioning and quality of life (Kiluk et al, ). Finally, the classification approach used was empirically driven.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that such out- comes do not predict functional, symptomatic or substance use-related improvement at 1 year follow-up. So additional outcomes, possibly related to change on the negative consequences of substance use [75], should be considered in future studies to better capture possible improvements and change processes.…”
Section: Discussionmentioning
confidence: 99%